A very typical family : a novel - Godfrey, Sierra (Sourcebooks Landmark, 2022)
"A propulsive contemporary women's fiction debut with dark humor and messy yet warm-hearted family dynamics, perfect for fans of Claire Lombardo's The Most Fun We Ever Had and Emma Straub's All Adults Here. All families are messy. Some are disasters. Natalie Walker is the reason her older brother and sister went to prison over 15 years ago. She fled California shortly after that fateful night and hasn't spoken to anyone in her family since. Ten years later--on the same day her boyfriend steals her dream job out from under her--Natalie receives a letter from a lawyer saying her estranged mother has died and left the family's historic Santa Cruz house to her. Sort of. The only way for Natalie and her siblings to inherit is for all three adult children to come back and claim it--together. Natalie drives cross-country to Santa Cruz with her willful cat in tow expecting to sign some papers, see siblings Lynn and Jake briefly, and get back to sorting out her life in Boston. But Jake, now an award-winning ornithologist, is missing. And Lynn, working as an undertaker in New York City, shows up with a teenage son. While Natalie and her nephew look for Jake--meeting a very handsome marine biologist who immediately captures her heart--she unpacks the guilt she has held onto for so many years, wondering how-or if-she can salvage a relationship with her siblings after all this time. A Very Typical Family navigates the messy yet warm-hearted journey of a family struggling to find each other again. Written with delightfully dark humor and characters you can't help but cheer for, this debut from Sierra Godfrey will have you reveling in the power of family and second chances. No one can change the past, but every day is an opportunity to choose your future"--